Instrumen Tes Keterampilan Berbicara dalam Pembelajaran Bahasa Arab bagi Peserta Didik di MTs Alfitiyan - Alvira Pranata (Armala, 2023)
This study aims to determine the test instrument used in Arabic speaking skills in students. This research uses Mixed Methods which combines quantitative research and qualitative research. the sample in this study was class VII A, totaling 30 students selected by random sampling. The results of this study were obtained from tests of speaking skills, observations and interviews with students. Based on the data analysis, the results were obtained: The Arabic speaking skills of class VII students were 73.96% or included in the sufficient category. Factors that influence the Arabic speaking skills of class VII students, namely the lack of readiness in teaching vocabulary and memorization in learning Arabic, the lack of interest that students have and the lack of practice in Arabic speaking skills which is one of the factors, for this the test instrument used used aims to explore and analyze students' abilities in Arabic speaking skills, with written and oral test instruments used on students. Keywords: Test, speaking skills, Arabic